EFFECTORANNOTATOR, A SCRIPT FOR AN EASY AND AUTOMATED IDENTIFICATION AND COMPARISON OF THE TYPE III SECRETION SYSTEM EFFECTORS OF PSEUDOMONAS SYRINGAE. (2016) - Marcelletti, Simone; Scortichini, Marco; Firrao, Giuseppe
No abstract available